Muscle RING‐finger 2 and 3 maintain striated‐muscle structure and function. Issue 2 (7th September 2015) - Lodka, Dörte; Pahuja, Aanchal; Geers‐Knörr, Cornelia; Scheibe, Renate J.; Nowak, Marcel; Hamati, Jida; Köhncke, Clemens; Purfürst, Bettina; Kanashova, Tamara; Schmidt, Sibylle; Glass, David J.; Morano, Ingo; et al.
Abstract: Background: The Muscle‐specific RING‐finger (MuRF) protein family of E3 ubiquitin ligases is important for maintenance of muscular structure and function. MuRF proteins mediate adaptation of striated muscles to stress. MuRF2 and MuRF3 bind to microtubules and are implicated in sarcomere formation with noticeable functional redundancy. However, if this redundancy is important for muscle function in vivo is unknown. Our objective was to investigate cooperative function of MuRF2 and MuRF3 in the skeletal muscle and the heart in vivo . Methods: MuRF2 and MuRF3 double knockout mice (DKO) were generated and phenotypically characterized. Skeletal muscle and the heart were investigated by morphological measurements, histological analyses, electron microscopy, immunoblotting, and real‐time PCR. Isolated muscles were subjected to in vitro force measurements. Cardiac function was determined by echocardiography and working heart preparations. Function of cardiomyocytes was measured in vitro . Cell culture experiments and mass‐spectrometry were used for mechanistic analyses. Results: DKO mice showed a protein aggregate myopathy in skeletal muscle. Maximal force development was reduced in DKO soleus and extensor digitorum longus . Additionally, a fibre type shift towards slow/type I fibres occurred in DKO soleus and extensor digitorum longus . MuRF2 and MuRF3 ‐deficient hearts showed decreased systolic and diastolic function. Further analyses revealed an increased expression of the myosin heavy chain isoform beta/slow and disturbed calcium handling as potential causes for the phenotype in DKO hearts. Conclusions: The redundant function of MuRF2 and MuRF3 is important for maintenance of skeletal muscle and cardiac structure and function in vivo .